Peran Bahasa Dalam Pemertahanan Identitas Budaya di Tengah Krisis Lingkungan Pada Novel “Chikyu ni Chiribamerarete” karya Tawada Yoko - Fitriana Puspita Dewi (Vocational College of Diponegoro University, 2026)
This study examines the representation of language as a strategy for cultural identity preservation amid environmental crisis in Tawada Yoko's dystopian novel Chikyu ni Chiribamerarete (2021). Using an ecocritical framework from Cheryll Glotfelty and Lawrence Buell, alongside Tawada's concept of exophony and Jan Assmann's cultural memory theory, this research applies close reading and hermeneutic interpretation to analyze the protagonist Hiruko's responses to the extinction of Japan due to environmental catastrophe. The findings reveal that environmental destruction triggers not only physical collapse but also the disintegration of language and cultural identity, turning Hiruko into a linguistic refugee. In response, Hiruko employs three strategies: creating a homemade language (Pan-Ska) as exophonic resistance, preserving Japanese mythology through Kamishibai storytelling, and using nostalgic vocabulary to reconstruct emotional bonds with a lost homeland. This study concludes that language serves as the final vessel of place attachment and cultural continuity, and that emotional ties to a place persist even after its physical extinction.